Science learning in a leisure setting - Falk, John H.; Storksdieck, Martin (Journal of research in science teaching, 2010)
Most people visit a science center in order to satisfy specific leisure‐related needs; needs which may or may not actually include science learning. Falk proposed that an individual's identity‐related motivations provide a useful lens through which to understand adult free‐choice science learning in leisure settings. Over a 3‐year period the authors collected in‐depth data on a random sample of visitors to a large recently opened, hands‐on, interactive science center; collecting information on why people visited, what they did within the science center, what they knew about the subject presented upon entering and exiting, and what each individual's long‐term self‐perceptions of their own learning was. Presented is a qualitative analysis of visitor interviews collected roughly 2 years after the initial visit. Although there was evidence for a range of science learning outcomes, outcomes did appear to be strongly influenced by visitor's entering identity‐related motivations. However, the data also suggested that not only were the motivational goals of a science center visit important in determining outcomes, so too were the criteria by which visitors judged satisfaction of those goals; in particular whether goal satisfaction required external or merely internal validation. The implications for future informal science education research and practice are discussed. © 2009 Wiley Periodicals, Inc. J Res Sci Teach 47:194–212, 2010